Imaging Flow Cytometry to Assess Antigen‐Presenting‐Cell Function. (6th March 2019) - Markey, Kate A.; Gartlan, Kate H.
Abstract: This unit describes methods for quantifying phagocytosis and imaging the immunological synapse between T cells and antigen‐presenting cells (APCs), with both techniques delivering valuable information about APC function. These aspects of APC biology have traditionally been challenging to quantify, and imaging flow cytometry, which harnesses the high‐throughput nature of flow cytometry combined with the capacity of microscopy to deliver spatial localization, facilitates analysis of these APC functions in a fashion that was previously not possible. Imaging flow cytometry allows large numbers of events to be captured and large amounts of fluorescence data to be quantified at the physical location of markers of interest, both on the cell surface and in intracellular compartments, combining key features of traditional flow cytometry and fluorescence microscopy. © 2019 by John Wiley & Sons, Inc.